História de vida e formação de professores de História: narrativas de si e repercussões sobre a prática docente - Maciel, João Paulo Santana (Universidade Federal do Tocantins, 2020)
This work talks about life´s history and academic education of History teachers, their narratives and its repercussions on their teaching practice. Bringing as objectives: to know the narratives of life stories and History teacher forming of Elementary Education of the municipality of Imperatriz; to identify the experiences evidenced in these narratives, to analyze them in view of their repercussion in the pedagogical practice and, finally, to prepare and present to the Municipal Department of Education a methodological proposal for the training of History teachers. In addition, it will have as its axis the own production from the individual experiences, contextualized historically and socialized in group. These objectives start from the following guiding questions: what does the history teacher say about his / her life history and formation? And how do these experiences impact on your teaching practice? The methodology adopted to address this challenge is centered on the teacher and his / her lifelong experiences and teaching career. Thus, his autobiographical, written and spoken narratives were used as sources, which served as an object of analysis to understand how these aspects reverberate or even interfere with teaching practice. In view of the work accomplished, the discussion indicated that the experiences that marked the life of the teacher, including in the process of his formation, respond with amplitude for his performance as a teacher. That is, the day-to-day professional exercise is consistently delineated by the repercussions of those experiences that composed the real life of this teacher as an active subject and inserted in a certain historical context.